2015
DOI: 10.1088/1742-5468/2015/09/p09010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of relaxation processes in interacting vortex matter through a time-dependent correlation length

Abstract: Vortex lines in type-II superconductors display complicated relaxation processes due to the intricate competition between their mutual repulsive interactions and pinning to attractive point or extended defects. We perform extensive Monte Carlo simulations for an interacting elastic line model with either point-like or columnar pinning centers. From measurements of the space-and time-dependent height-height correlation function for lateral flux line fluctuations, we extract a characteristic correlation length t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The scaling only emerges for larger t/s, when the system has had sufficient time to overcome the initial large fluctuations that immediately follow the quench, and to enter the aging scaling regime. For interacting lines, the aging scaling regime will be cut short at very long times by the caging effect of the repulsive vortex interactions (also responsible for limiting the growth of r g ) [29]. The scaling form for simple aging given in (10) is a special case of the more general scaling form f C (t, s) ∼ [L(t)/L(s)] −λ C .…”
Section: Quenches From the Moving Into The Pinned Regimementioning
confidence: 99%
“…The scaling only emerges for larger t/s, when the system has had sufficient time to overcome the initial large fluctuations that immediately follow the quench, and to enter the aging scaling regime. For interacting lines, the aging scaling regime will be cut short at very long times by the caging effect of the repulsive vortex interactions (also responsible for limiting the growth of r g ) [29]. The scaling form for simple aging given in (10) is a special case of the more general scaling form f C (t, s) ∼ [L(t)/L(s)] −λ C .…”
Section: Quenches From the Moving Into The Pinned Regimementioning
confidence: 99%
“…For the case of random point defects, which is the only case considered in this paper, these pinning centers are randomly distributed and chosen independently for each layer. If one were to instead consider columnar defects aligned parallel to the magnetic field along the z direction, then one would repeat the same spatial distribution pattern for each layer [6,14,16].…”
Section: Implementation For Disordered Type-ii Superconductorsmentioning
confidence: 99%
“…Du et al observed that the voltage response to an externally applied current in a superconducting 2H-NbSe 2 sample depended on the pulse duration, and that was an evidence of the occurrence of physical aging in disordered superconducting materials [21]. On the numerical front, Pleimling and Täuber employed an elastic line model and Monte Carlo simulations to study magnetic flux lines in type-II superconductors analyzing their non-equilibrium relaxation properties, starting from somewhat artificial initial conditions where straight flux lines were randomly placed in the sample [22,23]. The resulting complex aging features (with identical initial conditions and parameter values) were subsequently confirmed in a very different microscopic representation of the non-equilibrium vortex kinetics through Langevin molecular dynamics [24].…”
Section: Introductionmentioning
confidence: 99%